Nursing Examinations: Promotion of Integrity and Prevention of Cheating. Issue 4 (July 2016) - Palmer, Janice L.; Bultas, Margaret; Davis, Renée L.; Schmuke, Ashley D.; Fender, Joshua B.
Abstract : Academic integrity is a concern in higher education. The authors describe the findings of a nursing faculty task force developed with the goal of reducing incidents of cheating on classroom examinations in a school of nursing. Following a review of the literature, a modified Delphi technique was used to prioritize the suggested strategies into recommendations for faculty to follow. The findings and recommendations from the task force are presented and serve as a guide for nursing faculty in implementing measures to promote academic integrity during classroom examinations.